ANALYSIS OF THE IMPACT OF FINANCIAL RESISTANCE AND FINANCIAL PERFORMANCE ON PT PERTAMINA’S FINANCIAL RESILIENCE DURING THE ECONOMIC CRISIS - Pranata, Natasha Anjanette; Tyas, Hesti Ning; Wulandari, Amalia Dewi; R. Pandin, Maria Yovita (JEA17: Jurnal Ekonomi Akuntansi, 2024)
The object of research that we will use is PT. Pertamina is listed on the Indonesian Stock Exchange. The purpose of this study is to determine the impact of resistance and financial performance on the resilience of PT. Pertamina during the economic crisis. This research wasconducted using data in the IDX Annual Report to determine PT PERTAMINA's financial resilience during the economic crisis. Additionally crucial to enhancing the resiliency or soundness of financial institutions is effective risk management. Posing obstacles to the development of financial markets and institutions resilience. To maintain general economic stability and health, it is crucial to strengthen the resilience of financial markets and financial institutions. The findings demonstrate the beneficial influence of financial resilience on economic performance and its potential to lessen the effect of the possibility of a global recession on businesses and the overall economy. The research methodology we